Post-productivism and rural revitalization in China: Drivers and outcomes - WU, Meiling (Institutional Knowledge at Singapore Management University, 2024)
We propose that post-productivism offers a useful analytical framework for understanding the multi-scalar and diverse changes that are taking place in China’s rural revitalization. As a theoretical framework that emerged from the study of rural changes in the Global North, the applicability of post-productivism in the Global South has been contested. This paper offers the first comprehensive analysis of the emergence of post-productivism in rural China and uses post-productivism as a framework to conceptualize a wide range of changes in China’s rural revitalization. We conceptually clarify the driving forces that give rise to post-productivism and the outcomes these drivers produce. The two key drivers of post-productivism in China have been: 1) discontents with productivist agriculture from the state, urban consumers, and rural communities, which manifested in a shift in government’s policy priority from agricultural production to ecological restoration, urban consumers’ demands for “quality food”, and rural producers’ demands for a “quality life”, and 2) urbanites’ desire to experience the rural idyll, which translated into demands on rural space for urban consumption. We use seven representative cases to illustrate the various types of post-productivism that the two drivers have generated in rural China. These cases underscore that the transition to post-productivism is a key characteristic of China’s rural revitalization.